Mental health disorders among ovarian cancer survivors in a population‐based cohort. (30th June 2022) - Hu, Siqi; Baraghoshi, David; Chang, Chun‐Pin; Rowe, Kerry; Snyder, John; Deshmukh, Vikrant; Newman, Michael; Fraser, Alison; Smith, Ken; Peoples, Anita R.; Gaffney, David; Hashibe, Mia
Abstract: Background: Ovarian cancer is the fifth most common female cancer in the United States. There have been very few studies investigating mental health diagnoses among ovarian cancer survivors with long‐term follow up. The aim of this study is to examine the incidence of mental illness among ovarian cancer survivors compared to a general population cohort. A secondary aim is to investigate risk factors for mental illnesses among ovarian cancer survivors. Patients and methods: Cohorts of 1689 ovarian cancer patients diagnosed between 1996 and 2012 and 7038 women without cancer matched by age and birth state from the general population were identified. Mental health diagnoses were identified from electronic medical records and statewide healthcare facilities data. Cox proportional hazard models were used to estimate hazard ratios (HRs). Results: Ovarian cancer survivors experienced increased risks of mental illnesses within the first 2 years after cancer diagnosis (HR = 3.55, 95% CI = 3.04–4.14). The risks of depression among ovarian cancer survivors were nearly 3‐fold within the first 2 years of cancer diagnosis (HR = 2.59, 95% CI = 1.94–3.47), and 1.69‐fold at 2–5 years after cancer diagnosis (HR = 1.69, 95% CI = 1.18–2.42). Ovarian cancer survivors experienced an 80% increased risk of death with a mental illness diagnosis (HR = 1.80, 95% CI = 1.48–2.18) and a 94% increased risk of death with a depression diagnosis (HR = 1.94, 95% CI = 1.56–2.40). Conclusions: Higher risks of mental illnesses were observed among ovarian cancer survivors throughout the follow‐up periods of 0–2 years and 2–5 years after cancer diagnosis. Multidisciplinary care is needed to monitor and treat mental illnesses among ovarian cancer survivors.